Insulin resistance and muscle insulin receptor substrate‐1 serine hyperphosphorylation. Issue 12 (3rd December 2014) - Stuart, Charles A.; Howell, Mary E. A.; Cartwright, Brian M.; McCurry, Melanie P.; Lee, Michelle L.; Ramsey, Michael W.; Stone, Michael H.
Abstract Insulin resistance in metabolic syndrome subjects is profound in spite of muscle insulin receptor and insulin‐responsive glucose transporter (GLUT4) expression being nearly normal. Insulin receptor tyrosine kinase phosphorylation of insulin receptor substrate‐1 (IRS‐1) at Tyr896 is a necessary step in insulin stimulation of translocation of GLUT4 to the cell surface. Serine phosphorylation of IRS‐1 by some kinases diminishes insulin action in mice. We evaluated the phosphorylation status of muscle IRS‐1 in 33 subjects with the metabolic syndrome and seventeen lean controls. Each underwent euglycemic insulin clamps and a thigh muscle biopsy before and after 8 weeks of either strength or endurance training. Muscle IRS‐1 phosphorylation at six sites was quantified by immunoblots. Metabolic syndrome muscle IRS‐1 had excess phosphorylation at Ser337 and Ser636 but not at Ser307, Ser789, or Ser1101. Ser337 is a target for phosphorylation by glycogen synthase kinase 3 (GSK3) and Ser636 is phosphorylated by c‐Jun N‐terminal kinase 1 (JNK1). Exercise training without weight loss did not change the IRS‐1 serine phosphorylation. These data suggest that baseline hyperphosphorylation of at least two key serines within muscle IRS‐1 diminishes the transmission of the insulin signal and thereby decreases the insulin‐stimulated translocation of GLUT4. Excess fasting phosphorylation of muscle IRS‐1 at Ser636 may be a major cause of the insulin resistance seen in obesity and might prevent improvement in insulin responsiveness when exercise training is not accompanied by weight loss.